MiR-155 Induction by Microbes/Microbial Ligands Requires NF-κB-Dependent de novo Protein Synthesis - Tridandapani, Susheela; Cremer, Thomas J.; Fatehchand, Kavin; Shah, Prexy; Gillette, Devyn; Patel, Hemal; Marsh, Rachel L.; Besecker, Beth Y.; Rajaram, Murugesan V.; Kanneganti, Thirumala-Devi; Schlesinger, Larry; Butchar, Jonathan P. (Frontiers in Cellular and Infection Microbiology, 2012)
MiR-155 regulates numerous aspects of innate and adaptive immune function. This miR is induced in response to toll-like receptor ligands, cytokines, and microbial infection. We have previously shown that miR-155 is induced in monocytes/macrophages infected with Francisella tularensis and suppresses expression of the inositol phosphatase SHIP to enhance activation of the PI3K/Akt pathway, which in turn promotes favorable responses for the host. Here we examined how miR-155 expression is regulated during infection. First, our data demonstrate that miR-155 can be induced through soluble factors of bacterial origin and not the host. Second, miR-155 induction is not a direct effect of infection and it requires NF-κB signaling to up-regulate fos/jun transcription factors. Finally, we demonstrate that the requirement for NF-κB-dependent de novo protein synthesis is globally shared by microbial ligands and live bacteria. This study provides new insight into the complex regulation of miR-155 during microbial infection.